A Historical Overview of Scandinavian Protestantism up to the 19th Century - Liza Primc (Edinost in Dialog, 2023)
This paper provides a historical overview of the development of Protestantism in the Scandinavian countries up to the 19th century. Like the rest of Europe, the Reformation reached Scandinavia in the 16th century. It differs from other regions that have embraced Protestantism in that the new religious movement was imbued with a national identity and integrated into the highest levels of state power. The Church played a central role in the life of the citizens, not only as a religious and socio-cultural but also as a political institution. The established Lutheran state churches became the centre of the social life and, as a religious-political force, have been actively involved in the governance of the state (co-legislative and executive power, control of state education, administrative role of dioceses and parishes) until the 21st century.